Transformation and sources of growth in Southeast Asian agriculture - Joshi, Pramod Kumar; Roy, Devesh; Pandey, Ghanshyam; Birthal, Pratap Singh (International Food Policy Research Institute, 2019)
Over the past few decades, the agricultural sector of Southeast Asia has experienced robust growth and undergone a structural transformation albeit differentially across the countries in the region. The main aims of this paper are to understand the process of transformation and sources of growth in agriculture in the broader context of economy-wide changes in domestic and international markets, and to suggest technological, institutional and policy measures for faster, efficient and sustainable growth. Our findings show faster growth in agriculture in comparatively low-income countries, with technological change, area expansion and diversification being the main drivers. On the other hand, agricultural growth in high-income countries has been relatively slow, and driven by price increases, mainly of the export-oriented commercial crops, such as oil-palm, rubber and coconut; and also, by area expansion. In view of the fixed supply of land and high volatility in global food prices, area and price driven growth is unlikely to sustain in the long-run. For efficient, sustainable and inclusive growth, the recourse has to be with exploiting potential of (i) existing and frontier technologies, by investing more in agricultural research and extension systems, and (ii) diversification of production portfolio towards higher-value food commodities by strengthening institutions that link farmers to remunerative markets; and investing in post-harvest infrastructure for food processing.